Influence of Social Cultural Factors on Adoption of Sanitation Systems in Rural Communities: : Case of Tharaka-North Sub-County, Tharaka-Nithi County, Kenya. - KAYOGO, MUGENDI EDWIN MUTHONI; Kayogo, Mugendi Edwin Muthoni (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The Sustainable Development Goal agenda 6.2 targets to achieve universal basic sanitation and hygiene ( United Nations 2018). This paper assessed and examined the influence of social cultural factors on adoption of sanitation systems in rural communities. Approaches instituted by the government to promote improved sanitation and creation of awareness have not shown complete effectiveness in triggering sustainable sanitation behavior. Therefore the results from the research are essential in understanding the factors that influence the willingness and ability to invest in sanitation in combating and reversing the impacts of inadequate sanitation in rural communitie.The article was based on field research that employed convergent research design where both qualitative and quantitative data was gathered simultaneously. Quantitative data was gathered using structured questionnaires from 100 household heads selected using stratified proportionate simple random sampling techniques. Qualitative data was collected using an interview guide from a purposively selected focus group consisting of 7 participants. The findings were organized into themes and presented in narratives. Quantitative data was analyzed the statistical package for social sciences (SPSS) version 25 which generated descriptive and inferential statistics to unveil the relationship between variables from the findings, the adoption of unimproved toilets was the main form of sanitation system, covering a mean of 2. 9807.A unit increase in traditions led to a 0.029 decrease in adoption of sanitation systems (p.value=0.009) in the rural communities. A unit increase in gender roles led to a 0.142 increase in adoption of sanitation practices (p.value=0.001). Residents believed that faeces left in the open could be used for witchcraft purposes, a tradition that had a positive impact in eradication open defecation. Some religious denominations like the Kavonikia and Agendi associated diarrhea with demons other than the poor sanitation which was seen to facilitate poor sanitation practices. Social-cultural factors such as presence of toilets , knowledge ,gender, religion, beliefs and traditions influenced adoption of sanitation systems. The study recommended that the Community Led Total Sanitation (CLTS) strategy should target both open defecation and enlighten residents on the dangers of adopting unimproved latrines. The study also recommended that inclusion of women in household sanitation matters to ensure adoption of women and children friendly household sanitation facilities and incorporation of religious leaders as advocates of sanitation systems alongside demographic, psychosocial and environmental factors.